Determinants of Food Security in Rice-Surplus Districts of North Sumatra: An Integrated Panel Data and Structural Equation Modeling Approach - Mitra Musika Lubis; Koko Junaidi; Safruddin Safruddin (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the factors influencing food security in rice-surplus districts of North Sumatra, Indonesia, during 2018–2023. Using secondary panel data, we apply Fixed Effect Models and Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships among rice availability, consumption, and food security. The availability of rice is significantly influenced by production levels, market prices, harvested area, and consumption patterns, while land productivity has no significant effect—suggesting inefficiencies in translating higher yields into accessible supply. Rice consumption is shaped by production, income, and population size but remains unaffected by price fluctuations. PLS-SEM findings reveal that food availability enhances access to food but can negatively affect nutrient absorption and food security directly, possibly due to limited dietary diversity or inadequate nutrition knowledge. However, access and absorption act as key mediators, ultimately improving overall food security. These results emphasize that increasing food availability alone is insufficient. Effective policies must also promote equitable access and improved nutrient utilization to ensure sustainable food security outcomes. By clarifying the complex linkages between food production, distribution, and utilization in rice-abundant regions, this study offers strategic insights for designing integrated, region-specific food security policies.